1996
DOI: 10.5547/issn0195-6574-ej-vol17-no1-1
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of SO2, NOx, and CO2, Emissions from Energy Use of Major Economic Sectors in Taiwan

Abstract: In this paper we use the Divisia index approach to decompose emission changes of SO2, NOx and CO2 from major economic sectors in Taiwan during 1980 to 1992. The study highlights the interrelationships between energy use and environmental quality, and provides insights for policy making. The emission changes are decomposed into five components-pollution coefficient, fuel mix, energy intensity, economic growth and industrial structure. Of all components analyzed, economic growth had the largest positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 11 publications
1
25
2
Order By: Relevance
“…IDA applies the index number concept in decomposition, and it has been universally used by scholars. For example, Lin and Chang (1996) applied the Divisia index approach to decompose emission of SO 2 , NO x and CO 2 from major economic sectors in Taiwan during 1980 to 1992. They revealed that economic growth had the leading positive effect on emission changes.…”
Section: Introductionmentioning
confidence: 99%
“…IDA applies the index number concept in decomposition, and it has been universally used by scholars. For example, Lin and Chang (1996) applied the Divisia index approach to decompose emission of SO 2 , NO x and CO 2 from major economic sectors in Taiwan during 1980 to 1992. They revealed that economic growth had the leading positive effect on emission changes.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies address sulphur dioxide emissions (Lin and Chang 1996;Shrestha and Timilsina 1997;Viguier 1999); among these, two (Shrestha and Timilsina 1997;Viguier 1999) address the emission intensity of individual energy sources, including coal, as a constant over time and focus only on changes in the energy mix-that is, the inter-energy composition of oil, gas, coal and non-fossil fuel energies. Lin and Chang (1996), however, find a continuous decrease in pollution intensity and attribute it to substitution for imported low-sulphur coal and 'desulphurisaton' of fuel oil, in the case of Taiwan. No study has, however, been done from the perspective of a clean future for fossil-fuel energy, and coal in particular.…”
Section: Emission Intensity Trendsmentioning
confidence: 99%
“…Labor price index Energy price index Sources: IEA (1990, 1992) and Statistics Sweden (1981, 1985, 1989, 1992, and 1996 18 The t-value of -1.55 corresponds to a p-value of 0.1465.…”
Section: Energy Effectivenessmentioning
confidence: 99%
“…There are several studies done on carbon dioxide with this method, e.g., Ang and Choi (1997) and Casler and Rose (1998). Lin and Chang (1996) did a study on energy-induced gas emissions with respect to sulfur in Taiwanese industry. However, earlier decomposition analyses were limited in their direct policy conclusions; i.e., they did not relate emissions-changes to actual economic factors, such as tax changes and emissions-related regulations.…”
Section: Introductionmentioning
confidence: 99%